2018
DOI: 10.1007/s12640-018-9870-x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Neurotoxicity Following Fluoride Exposure from Gestational Through Adult Ages in Long-Evans Hooded Rats

Abstract: At elevated levels, fluoride (F−) exposure has been associated with adverse human health effects. In rodents, F− exposure has been reported to induce deficits in motor performance and learning and memory. In this study, we examined Long-Evans hooded male rats maintained on a standard diet (20.5 ppm F−) or a low F− diet (3.24 ppm F−) with drinking water exposure to 0, 10, or 20 ppm F− from gestational day 6 through adulthood. At postnatal day 25, brain F− levels were 0.048 or 0.081 μg/g and femur 235 or 379.8 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…Male pups were exposed throughout adulthood and underwent neurobehavioral testing using different paradigms to assess learning and memory (NTP 2015). No exposure-related differences in motor, sensory, or learning and memory performance (running wheel, open-field activity, light/dark place preference, elevated plus maze, pre-pulse startle inhibition, passive avoidance, hot-plate latency, Morris water maze (MWM) acquisition, probe test, reversal learning, and Y-maze) were observed with either of the two exposure levels investigated (McPherson et al 2018). Therefore, a LOAEL and a doseresponse assessment could not be established.…”
Section: Neurobehavioral Studies and Neurotoxicitymentioning
confidence: 96%
See 4 more Smart Citations
“…Male pups were exposed throughout adulthood and underwent neurobehavioral testing using different paradigms to assess learning and memory (NTP 2015). No exposure-related differences in motor, sensory, or learning and memory performance (running wheel, open-field activity, light/dark place preference, elevated plus maze, pre-pulse startle inhibition, passive avoidance, hot-plate latency, Morris water maze (MWM) acquisition, probe test, reversal learning, and Y-maze) were observed with either of the two exposure levels investigated (McPherson et al 2018). Therefore, a LOAEL and a doseresponse assessment could not be established.…”
Section: Neurobehavioral Studies and Neurotoxicitymentioning
confidence: 96%
“…A number of studies also reported such effects in rats at 2-50 mg/L fluoride [corresponding to 0.1-2.5 mg/kg b.w./day applying EFSA default conversion factors (EFSA 2012)]. However, many of these findings occurred in the presence of motor dysfunction or general toxicity, thus diminishing confidence in any conclusion regarding learning deficits (McPherson et al 2018;NTP 2016). Overall, the systematic review by the NTP reported a low to moderate level of evidence for adverse effects on learning and memory in exposed animals with fluoride concentrations substantially higher than 0.7 mg/L (NTP 2016).…”
Section: Neurobehavioral Studies and Neurotoxicitymentioning
confidence: 99%
See 3 more Smart Citations